PENGARUH KONDISI KEUANGAN, PERTUMBUHAN PERUSAHAAN, DAN REPUTASI AUDITOR PADA PENGUNGKAPAN OPINI AUDIT GOING CONCERN - MERIANI, NI PUTU; AYU KRISNADEWI, KOMANG (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 7 No 1 (2012))
Audit report with modification of going concern indicates that in auditor’s opinion there is a risk that auditee could not survive. This going concern modification is not expected by companies because it would decrease public trust on the company’s image. This research aims to investigate the impact of financial condition, company growth, and auditor reputation on going concern audit opinion. The research object includes manufacturer listed on Indonesia Stock Exchange during 2008-2010 with 78 observations obtained using purposive sampling method. Data then is analyzed using logistic regression analysis. The result shows that the financial condition proxied by bankruptcy prediction model affect going concern auditor opinion negatively and significantly. While company size which is proxied by sales growth and auditor reputation which is proxied by audit firm size do not significantly affect the opinion.
Keywords: financial condition, company growth, auditor reputation, going concern opinion